2013
DOI: 10.1155/2013/283462
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Phytochemicals in Tissues from Sclerocarya birrea by HPLC-MS and Their Link with Antioxidant Activity

Abstract: High performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was employed to investigate the differences in phytochemicals in roots, bark, and leaf of Sclerocarya birrea (marula) for methanol and water extracts that exhibited the best antioxidant activities. As many as 36 compounds were observed in the extracts of these tissues of which 27 phenolic compounds were tentatively identified. The HPLC-MS/MS results showed flavonoid glycosides were prominent in leaf extracts while the galloylated tann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…The Sclerocarya birrea tree, known as marula tree, is indigenous to most parts of the Northern regions of Ghana and often referred to as the "tree of life" due to its ability to provide two fundamental human needs; that is, food and medicine. The marula tree is taxonomically derived from the Anacardiaceae plant family to which belong the mango, cashew and pistachio nut, and it is an indigenous, fruit-bearing tree of sub-Saharan Africa at low altitudes and can reach up to 20 m in height and 1.2 m in diameter (Russo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sclerocarya birrea tree, known as marula tree, is indigenous to most parts of the Northern regions of Ghana and often referred to as the "tree of life" due to its ability to provide two fundamental human needs; that is, food and medicine. The marula tree is taxonomically derived from the Anacardiaceae plant family to which belong the mango, cashew and pistachio nut, and it is an indigenous, fruit-bearing tree of sub-Saharan Africa at low altitudes and can reach up to 20 m in height and 1.2 m in diameter (Russo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The marula tree has gained attention in numerous chemical, biological and environmental investigations since 1906 and has been identified as one of five fruit tree species that should be integrated in the domestication process in African farming system (Russo et al, 2013), for its usage as source of food and medicine and its potential to increase income in rural communities. The barks, leaves and roots of S. birrea have been traditionally used to treat some human ailments such as dysentery, fevers, malaria, diarrhea, stomach problems, rheumatism, sore eyes, infertility, headaches, toothache and body pains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution and allocation of the nutrients in the leaves, bark and fruit indicate the capacity of the plants to obtain, transport and store the nutrients (Zhang et al 2015). However, the mineral distribution in the parts of a plant may vary because of climate, soil composition or nutrient level, harvest time, genotypes, preparation method and maturity level (San et al 2009). Vitamin analysis showed that the fruit contains the highest amount of vitamin E; the bark had the highest level of vitamin C; and the leaves contain the highest amount of vitamin A. Vitamin E is a fat-soluble vitamin well known for its high antioxidant potency (Ye et al 2013).…”
Section: Contents Of Minerals and Antioxidant Vitamins In C Cujetementioning
confidence: 99%
“…The results of our study indicate that the leaves contain the highest TPC levels followed by the bark and fruit (p<0.05) ( Table 2). This finding is most likely due to relatively higher abundance of unbound low molecular weight polar phenolic compounds in the leaves compared to that in the bark and fruit (Ghazi et al 2012;Russo et al 2013). Moreover, bark and fruit usually contain high levels of structural polysaccharides that bind high proportion of polyphenols thus masking their detection in the assay of phenolic compounds (Perez-Jimenez & Saura-Calixto 2005).…”
Section: Quantification Of Total Phenolic and Antioxidant Activitymentioning
confidence: 99%